Synergistic application of cardiac sympathetic decentralization and comprehensive psychiatric treatment in the management of anxiety and electrical storm - Khalsa, Sahib S.; Ajijola, Olujimi A.; Shahabi, Leila; Bystritsky, Alexander; Naliboff, Bruce D.; Shivkumar, Kalyanam (Frontiers in Integrative Neuroscience, 2014)
We report here, for the first time, two cases demonstrating a synergistic application of bilateral cardiac sympathetic decentralization and multimodal psychiatric treatment for the assessment and management of anxiety following recurrent Implantable Cardioverter Defibrillator (ICD) shocks. In a first case the combination of bilateral cardiac sympathetic decentralization (BCSD), cognitive behavioral psychotherapy and anxiolytic medication was sufficient to attenuate the patient’s symptoms and maladaptive behaviors, with a maintained benefit at 1 year. Among the more prominent subjective changes, we observed a decrease in aversive interoceptive sensations, particularly of the heartbeat following BCSD. The patient continued to experience cognitive threat appraisals on a frequent basis, although these were no longer incapacitating. In a second case, we report the effect of BCSD on autonomic tone and subjective state. In the post-lesion state we observed attenuated sympathetic responses to the valsalva maneuver, isometric handgrip and mental arithmetic stressor, including decreased systolic and diastolic blood pressure and decreased skin conductance. Collectively, these preliminary findings suggest that an integrative, multidisciplinary approach to treating anxiety disorders in the setting of ventricular arrhythmias and recurrent ICD shocks can result in sustained improvements in physical, psychological and functional status. These findings raise the possibility of a potential role for the stellate ganglion in the modulation of emotional experience and afferent transmission of interoceptive information to the central nervous system.